2022
DOI: 10.1364/ome.471672
|View full text |Cite
|
Sign up to set email alerts
|

ℏω versus ℏk: dispersion and energy constraints on time-varying photonic materials and time crystals [Invited]

Abstract: Photonic time-varying systems have attracted significant attention owing to their rich physics and potential opportunities for new and enhanced functionalities. In this context, the duality of space and time in wave physics has been particularly fruitful to uncover interesting physical effects in the temporal domain, such as reflection/refraction at temporal interfaces and momentum-bandgaps in time crystals. However, the characteristics of the temporal/frequency dimension, particularly its relation to causalit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 89 publications
0
13
0
Order By: Relevance
“…The realization of Photonic-Time-Crystals (PTCs) holds great potential to unlock new physics and phenomena applicable to non-resonant light amplification, tunable lasing, and a plethora of yet unexplored quantum light-matter interactions [1][2][3][4][5][6][7][8][9][10]. In order to realize photonic time-crystals operating in the optical frequency range, several challenges need to be addressed [11]. Most importantly, to achieve a detectable time-reflected signal and/or wide momentum bandgaps, the refractive index of the optical medium must be modulated by an appreciable amount (in the range 0.1-1) all while occurring in a time scale of a single optical cycle of the wave propagating in the medium.…”
Section: Introductionmentioning
confidence: 99%
“…The realization of Photonic-Time-Crystals (PTCs) holds great potential to unlock new physics and phenomena applicable to non-resonant light amplification, tunable lasing, and a plethora of yet unexplored quantum light-matter interactions [1][2][3][4][5][6][7][8][9][10]. In order to realize photonic time-crystals operating in the optical frequency range, several challenges need to be addressed [11]. Most importantly, to achieve a detectable time-reflected signal and/or wide momentum bandgaps, the refractive index of the optical medium must be modulated by an appreciable amount (in the range 0.1-1) all while occurring in a time scale of a single optical cycle of the wave propagating in the medium.…”
Section: Introductionmentioning
confidence: 99%
“…In the temporal analogs of photonic crystals, one can observe the momentum bandgaps inside which one can observe amplification of waves [25][26][27][28]. However, practical possibilities of time-varying photonics are strongly limited by the difficulties with fast and spatially uniform modulations of materials and by interference with common nonlinear effects [29].…”
Section: Introductionmentioning
confidence: 99%
“…[31,32]. While there are inherent constraints and technological challenges in the temporal modulation of constitutive parameters [33], experimental studies are continuing to progress, and recent results have demonstrated feasibility in this area [34][35][36].…”
Section: Introductionmentioning
confidence: 99%